The Effect of Job Satisfaction in Mediating the Relationship between Compensation, Tasks Competence and Commitment of Teachers ofSMA Don Bosco Padang - Kiwan, Martinus; Heryanto (Technium Social Sciences Journal, 2020)
This study aims to determinethe effect of Job Satisfaction in Mediating the Relationship between Compensation, Tasks Competence and Commitment of Teachers of SMA Don Bosco Padang as many as 64 people. Data were collected through questionnaires distributed to the entire population that could be used for analysis purposes. Hypothesis testing was carried out by using data analysis techniques through Path Analysis. The results of the data analysis show that of the (two) independent variables, Compensation has no significant effect. Menawhile, task competence has a significant effect on the Task Commitment variable (the dependent variable). Furthermore, the Compensation and Task CompetencyVariables have a significant effect on the Job Satisfaction variable as an intervening variable. Likewise, the Job Satisfaction variable also has a significant effect on performance. Both of the Independent Variables are eligible for the Mediation test. Job Satisfaction as an intervening variable has no influence between Compensation and Task Commitment. While Job Satisfaction as an intervening variable influences the Task Competence and the Task Commitment of Teachers of SMA Don Bosco Padang.The effect of compensation variable and career development to the commitment of the task in the first phase amounted described by value R2is 0.783 or 78.3%, when compared to the effect test of variable compensation and competency tasks to task commitment in the second stage by inserting a mediating variable work motivation where the effect described by the value R2is 0.783 or 84.6% or the increase of effect by incorporating variable job satisfaction as an intervening variable is 84.6% - 78.3%, or 6.3%